Foreign policy and orientation of the administration of independent Georgia (April-August 1991) - Shvelidze, Erekle (HISTORY, ARCHAEOLOGY, ETHNOLOGY, 2018)
This article examines the foreign policy orientation of the Independent Georgian government in April-August 1991. It analyses the relations Georgia had on international arena in that period. Georgia apparently had the most intensive relations with the existing and the former Republics of the USSR. It is worth mentioning that the best and most intensive were the relations with the Baltic Republics. The contacts with neighboring Armenia and Azerbaijan were also comparatively close. Georgia signed some treaties of political and economical character with them. The interrelations mutual solidarity were continued with the East European countries of so called “Socialist countries” which had already become the independent countries (Poland, Hungary, Bulgaria and others). Those countries could not at that time recognize Georgia’s independence but they tried as far as was possible, to express moral support; the economical-cultural relations were accented to develop. The National Government of the independent Georgia aimed to have interrelations with other countries of the world as well, which was difficult to realize because of the serious obstacles. The fact that Georgia’s independence was not recognized at that time represented the main barrier for the relations. The countries of the Western democracies avoided such official ties and the relations were limited to the humanitarian sphere. Despite this fact, the tendency of growing interest towards Georgia was obvious. Till the August 1991, Georgia’s new government also tries also to fix pro-western orientation. But the processes could not develop in positive way. The international political attitude to the former Soviet republic which had announced their independence, unfortunately changed in unfavorable way. Georgia appeared to be in political isolation. That was conditioned by the demands of the so called mainstream policy and global interests of the USA and USSR. The interests of Georgia were temporarily sacrificed to agreement between the Soviet Union and the USA on reduction of the strategic armament. It was also a mistake made by the Georgian  Government which took a hard-line postion towards the USA administration thus aiding to the process of international isolation of Georgia.